Use of the sampled electrical engineering device at diagnosing elements in electric systems; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Goldshtein E. I. (Power engineering, 2007)
Заглавие с титульного листа